2021
DOI: 10.1093/cercor/bhab048
|View full text |Cite
|
Sign up to set email alerts
|

Left-Handers Are Less Lateralized Than Right-Handers for Both Left and Right Hemispheric Functions

Abstract: Many neuroscientific techniques have revealed that more left- than right-handers will have unusual cerebral asymmetries for language. After the original emphasis on frequency in the aphasia and epilepsy literatures, most neuropsychology, and neuroimaging efforts rely on estimates of central tendency to compare these two handedness groups on any given measure of asymmetry. The inevitable reduction in mean lateralization in the left-handed group is often postulated as being due to reversed asymmetry in a small s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 48 publications
0
17
2
Order By: Relevance
“…No evidence of differences was found for any of these analyses. Not finding weaker lateralisation in left-lateralized left-handers contrasts with a recent finding that left-handers who are left-hemisphere dominant for language (about 70% of left-handers) are less lateralized compared to their right-handed counterparts (Johnstone et al, 2021). This difference may be attributed to the methods used, but also due to power ( n = 40 for this analysis compared to n = 74 in Johnstone et al).…”
Section: Discussioncontrasting
confidence: 97%
“…No evidence of differences was found for any of these analyses. Not finding weaker lateralisation in left-lateralized left-handers contrasts with a recent finding that left-handers who are left-hemisphere dominant for language (about 70% of left-handers) are less lateralized compared to their right-handed counterparts (Johnstone et al, 2021). This difference may be attributed to the methods used, but also due to power ( n = 40 for this analysis compared to n = 74 in Johnstone et al).…”
Section: Discussioncontrasting
confidence: 97%
“…In this sense, our findings most strongly reflect a right-handed population and should be interpreted with caution when applied to left-handed and ambidextrous populations. While there has been documentation of left handers demonstrating reduced functional lateralization in verbal and facial processing tasks compared to right-handed individuals ( Johnstone et al, 2021 ), differences in the white matter are less clearly documented. Some have found increased FA of the white matter when comparing the microstructure of left-handed to right-handed adults ( McKay et al, 2017 ), while other investigators have found no difference in the white matter microstructure between left- and right-handed children ( López-Vicente et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because the incidence rates are over twice as high in praxis compared to language (Króliczak et al, 2021a), the third, quite numerous group consists of individuals in whom the two functions dissociate, that is with atypically represented praxis and typical, i.e., left-lateralized language. (Further split of this group would require a completely different criterion, e.g., above or below zero for praxis; e.g., Johnstone et al, 2021. ) Finally, the fourth group consists of individuals who have both praxis and language atypically organized or lateralized, with no obvious criterion for dividing this group any further (because many individuals with right-lateralized praxis have balanced organization of language).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the vast majority of lefthanders still demonstrate-quite typical-left lateralization of language and praxis, and right lateralization of other functions, such as attention, face recognition or prosody processing in their brains (see Table 1 of Vingerhoets, 2019;cf. Króliczak, Piper et al, 2020; but see also Johnstone et al, 2021, who demonstrate that typical lefthanders are less lateralized than righthanders). As also shown quite recently, in the majority of ambidextrous individuals (mixedhanders), the praxis and language functions are quite typically represented, too (Króliczak et al, 2021a).…”
mentioning
confidence: 98%